Clinical profile and outcome of acute febrile encephalopathy in children - Hirekerur, Vikram L.; Gaikwad, Shahaji Y.; Kolewad, Aparna B. (International Journal of Contemporary Pediatrics, 2023)
Background: This prospective observational study aims at studying clinical profile of patients with acute febrile encephalopathy. Methods: This study was conducted in patients of acute febrile encephalopathy admitted in PICU at tertiary care centre during November 2019 to May 2021 in age group one month to 18 years. 35 patients satisfied the inclusion criteria. Results: 51.4% children belonged to age group less than 60 months and 40% children belonged to age group 61-120 months. Other than fever and altered sensorium (diagnostic criteria), seizures (74.3%), vomiting (60%), headache (22.9%) and refusal to feed (17.1%), were the major complaints. Raised ICT was found in 20 (57.1%). 20 (57.1%) patients had hyponatremia (Na+ <135). MRI brain abnormalities were found in 13 patients with majority finding being edema 8 (61.5%). 15 (62.5 %) patients had CSF cell count between 5-100/µl. 16 (45.7%) children presented with GCS score 10-12. In the present study, most common diagnosis was rickettsia encephalitis in 10 patients (28.6%) followed by Dengue encephalitis 6 (17.1%) and probable Viral encephalitis 6 (17.1%). There was no mortality in the present study. Conclusions: Seizure, headache and vomiting were the other common presenting features in a case of acute febrile encephalopathy. This indicates raised intracranial tension. Rickettsia followed by Dengue and probable Viral encephalitis were the common etiological diagnosis. Many cases are viral in nature and since no particular or highly effective therapy is available, early diagnosis, emergent treatment of raised intracranial pressure and hyponatremia and implementation of aggressive supportive care may reduce mortality and morbidity as in present study.